Primate Life Histories, Sex Roles, and Adaptability Essays in Honour of Linda M. Fedigan (Developments in Primatology: Progress and Prospects,, 2018)
Professor Linda M. Fedigan, Member of the Order of Canada and a Fellow of the Royal Society of Canada, has made major contributions to our understanding of the behavioural ecology of primates. Furthermore, Linda Fedigan pioneered and continues to advance scholarship on the role of women in science, as well as actively promoting the inclusion of women in the academy. A symposium in honour of her career was held in Banff (Alberta, Canada) in December 2016, during which former and current students and collaborators, as well as scientists with similar research interests, presented and discussed their work and their connections to Linda Fedigan. These presentations and discussions are here presented as chapters in this festschrift. The original works presented in this book are organized around four major research areas that have been greatly advanced and influenced by Linda Fedigan: Primate life histories Sex roles, gender, and science Primate-environment interactions Primate adaptation to changing environments.